Tissue repair, contraction, and the myofibroblast - Desmoulière, Alexis; Chaponnier, Christine; Gabbiani, Giulio (Wound repair and regeneration, 2005)
After the first description of the myofibroblast in granulation tissue of an open wound by means of electron microscopy, as an intermediate cell between the fibroblast and the smooth muscle cell, the myofibroblast has been identified both in normal tissues, particularly in locations where there is a necessity of mechanical force development, and in pathological tissues, in relation with hypertrophic scarring, fibromatoses and fibrocontractive diseases as well as in the stroma reaction to epithelial tumors. It is now accepted that fibroblast/myofibroblast transition begins with the appearance of the protomyofibroblast, whose stress fibers contain only beta- and gamma-cytoplasmic actins and evolves, but not necessarily always, into the appearance of the differentiated myofibroblast, the most common variant of this cell, with stress fibers containing alpha-smooth muscle actin. Myofibroblast differentiation is a complex process, regulated by at least a cytokine (the transforming growth factor-beta1), an extracellular matrix component (the ED-A splice variant of cellular fibronectin), as well as the presence of mechanical tension. The myofibroblast is a key cell for the connective tissue remodeling that takes place during wound healing and fibrosis development. On this basis, the myofibroblast may represent a new important target for improving the evolution of such diseases as hypertrophic scars, and liver, kidney or pulmonary fibrosis.